Phosphoinositides: lipid regulators of membrane proteins - Falkenburger, Björn H (Blackwell Science Inc, 2010)
Phosphoinositides are a family of minority acidic phospholipids in cell membranes. Their principal role is instructional: they interact with proteins. Each cellular membrane compartment uses a characteristic species of phosphoinositide. This signature phosphoinositide attracts a specific complement of functionally important, loosely attached peripheral proteins to that membrane. For example, the phosphatidylinositol 4,5-bisphosphate (PIP(2)) of the plasma membrane attracts phospholipase C, protein kinase C, proteins involved in membrane budding and fusion, proteins regulating the actin cytoskeleton, and others. Phosphoinositides also regulate the activity level of the integral membrane proteins. Many ion channels of the plasma membrane need the plasma-membrane-specific PIP(2) to function. Their activity decreases when the abundance of this lipid falls, as for example after activation of phospholipase C. This behaviour is illustrated by the suppression of KCNQ K(+) channel current by activation of M(1) muscarinic receptors; KCNQ channels require PIP(2) for their activity. In summary, phosphoinositides contribute to the selection of peripheral proteins for each membrane and regulate the activity of the integral proteins.